Ocular Effects of Niacin: A Review of the Literature - Domanico, Daniela (Med Hypothesis Discov Innov Ophthalmol, 2015)
Cystoid macular edema is a condition that involves the macula, caused by an accumulation of extracellular fluid in the macular region with secondary formation of multiple cystic spaces. This condition is provoked by a variety of pathological conditions such as intraocular inflammation, central or branch retinal vein occlusion, diabetic retinopathy and most commonly following cataract extraction, hereditary retinal dystrophies, and topical or systemic assumption of drugs. Niacin is a vitamin preparation usually used for the treatment of lipid disorders. The treatment with niacin, alone or in combination with other lipid-lowering agents, significantly reduces total mortality and coronary events and slows down the progression of and induces the regression of coronary atherosclerosis. Several cases of niacin-induced cystoid macular edema have been reported with different dosages.